1978
DOI: 10.1128/aac.14.3.495
|View full text |Cite
|
Sign up to set email alerts
|

Inosiplex for Localized Herpes Zoster in Childhood Cancer Patients: Preliminary Controlled Study

Abstract: By multiple criteria, inosiplex-a reputed stimulator of virus-sensitized lymphocytes-had no demonstrable therapeutic effects in a preliminary controlled study of patients with localized herpes zoster and cancer. Lymphocytes from the six drug-treated patients were no more responsive to varicella-zoster antigen and phytohemagglutinin than were lymphocytes from seven patients who received a placebo.Inosiplex (p-acetamidobenozoic acid salt of inosine-dimethylaminoisopropanol acid in a 1:3 molar ratio) is presently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…FELDMAN et al (1978) found that children with neoplasms who developed herpes zoster infection did not show improvement with inosiplex. Again reports have been both negative and positive.…”
Section: Inosiplex (Isoprinosine)mentioning
confidence: 99%
“…FELDMAN et al (1978) found that children with neoplasms who developed herpes zoster infection did not show improvement with inosiplex. Again reports have been both negative and positive.…”
Section: Inosiplex (Isoprinosine)mentioning
confidence: 99%